Answer:
8x - 20
Step-by-step explanation:
6(2x - 3) - 2(2x + 1)
Distribute
6(2x) -6( 3) - 2(2x) -2( 1)
12x -18 -4x -2
Combine like terms
12x -4x -18 -2
8x-20
Answer:
g(-1) = -5
g(2a+1) = 16a+11
Step-by-step explanation:
Substitute the given value into the function and evaluate.
So for g(x) = 8x+3
You substitute g(-1)
So g(-1) = 8(-1)+3
That is how you get -5
Then g(2a+1)
So g(2a+1) = 8(2a+1)+3
Thats how you get 16a+11
Hope this helps. Mark as brainlist
The answer would be 198/300. That simplified would be 33/50. If you want a percent, it would be 66%.